Studi Keunggulan Bersaing Destinasi Wisata Jawa Barat - Erislan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
One of the competitive advantages of tourist destinations can be measured through the sacrifices of tourists who are willing to leave their place of residence to travel long distances to a place they have visited, with the aim of gaining satisfaction and finding something they cannot find at home. The value of the sacrifice can be perceived in the form of reciprocity or benefit. The suitability of the benefits received when visiting must be in accordance with the sacrifices made by tourists. Fulfilling tourists' expectations of the destination will produce added value in tourists' perceptions which will lead to satisfaction and have implications for repeat visits to the destination continuously. Tourism development that is committed to providing the best experience to tourists when visiting destinations is the toughest challenge for tourist attraction managers. Apart from the different expectations of tourists which demand a variety of tours, good and unique service can also be a concept of competitive advantage in order to provide quality tourism that cannot be found in the environment where tourists live. In this research, we conducted a study to measure the extent to which the concept of competitive advantage above was identified and confirmed to tourists, so that we obtain a reality that describes whether a tourist attraction is managed well or not, which originates from tourists' perceptions. Thus, in the future, this study can be used as a reference in improving and developing tourist destination strategies.